Mexican Sycamore (Platanus mexicana) - Gary W. Knox (EDIS)
Mexican sycamore (Platanus Mexicana) is a fast growing, drought tolerant tree boasting smooth white and tan bark and large, maple-like leaves with velvety, silver undersides. Native to northeastern and central Mexico, this tree’s cold hardiness is not well defined. However, Mexican sycamore grows well as far north as USDA Cold Hardiness Zone 8b in Texas and Florida. This 2-page fact sheet was written by Gary W. Knox and published by the UF Department of Environmental Horticulture, June 2014.